Examen especial a la cuenta inversiones de la cooperativa Mushuc Runa Ltda, matriz Ambato, período del 01 de enero al 31 de diciembre del 2009 - Estrella Romero, Mayra Verónica (2014)
The information taken during the course of time of the investigation establishes that it’s important the application of a special exam, in the account investment of cooperation Mushuc Run Ltda, now that the application itself will allow the manager and its personal administrators, will decide with precision the fulfillment of existent politics for the management of the account investment, the reasonableness and trustworthiness of the referent figures in this account reflecting in financial estates and finally the correct decisions that facilitate fulfillment of all the measures and the objectives that were set out for the Cooperation. To obtain real and exact information while the running of the cooperation, we applied investigation techniques like: the interview, the same that were applied to the general manager, administrator, accountant and cashiers with the accomplishments of knowing the administration and functioning of the cooperation, and other techniques applied were the surveys, the ones that were directed at the associates, with the purpose of knowing the economic process in which will unravel the cooperation Mushuc Runa Ltda. Finally a special exam was applied, directed at the account investments, in which the propose is to demonstrate the transparency and truthfulness of the real corresponding figures, equally reflected in the financial estates, in which the exam will allow getting to the conclusion of the account investments reflects in a way that the transparency and truthfulness of its corresponding wages of the year 2009, the base that the diagnostic of the economic investments resources in its account.